Multifunctional admixture additive based on industrial solid waste as well as preparation and use methods thereof
The carbon nanotube-fly ash composite additive addresses uneven conductivity and hydrophilicity issues in concrete by forming a stable conductive and hydrophobic network, improving conductivity and durability while recycling fly ash, thus meeting the needs of specific applications.
Patent Information
- Application Number
- CN202411675778.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-11-22
AI Technical Summary
Existing concrete admixtures using carbon black powder result in uneven conductivity, increased water absorption, and reduced durability due to hydrophilicity, failing to meet the conductivity and hydrophobicity requirements in specific applications.
A multifunctional admixture additive based on a carbon nanotube-fly ash composite material is prepared by impregnating fly ash with nickel nitrate, reacting under controlled conditions to grow carbon nanotubes, and treating fly ash with stearic acid to enhance hydrophobicity, then integrating it with cement and aggregates to form a conductive and waterproof concrete.
The composite material ensures uniform conductivity and improved durability by forming a stable conductive network and hydrophobic layer, enhancing the overall performance of concrete while recycling industrial waste and reducing production costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of building materials, and in particular relates to a multifunctional admixture additive based on industrial solid waste and a preparation and use method thereof. Background Art
[0002] Fly ash is one of the main solid wastes produced by coal-fired power plants during the combustion of coal. When coal is burned in the boiler, the minerals in the coal will melt at high temperatures and be discharged with the flue gas. These tiny particles are captured and collected when passing through the dust removal device, forming fly ash. The chemical composition of fly ash varies depending on the type of coal burned and regional differences, but generally contains silica, alumina, iron oxide, calcium oxide, etc. Silica is usually the main component of fly ash, which can account for more than 50% of the total. According to my country's coal consumption, burning 1 ton of coal produces about 250 to 300 kg of fly ash. If a large amount of fly ash is not controlled or treated, it will cause air pollution and silt up rivers when it enters the water body. It is now widely used in the preparation of building materials such as concrete.
[0003] Traditional concrete is widely used in the construction industry due to its insulating properties. However, in certain specific application scenarios, such as heated pavement, lightning protection facilities, electromagnetic shielding, etc., ordinary concrete cannot meet the needs. In order to overcome this limitation, researchers began to explore how to make concrete conductive. In cold areas, conductive concrete can be used for paving roads to prevent snow and ice accumulation by heating with electricity, or for building buildings that require electromagnetic shielding effects, such as data centers and laboratories. The lightning protection system of buildings can use conductive concrete to improve efficiency. By integrating sensors, conductive concrete can be used to monitor structural health, such as crack detection, etc. In corrosive environments, conductive concrete can also provide corrosion protection.
[0004] CN107082602B discloses a non-fired concrete and a preparation method thereof, comprising the following components expressed by weight: 160-320 parts of cement; 100-140 parts of admixtures; 700-900 parts of non-fired fine aggregate; 950-1150 parts of non-fired coarse aggregate; 1.7-2.3 parts of conductive enhancer; 1.4-1.9 parts of polyacrylonitrile carbon fiber; 5-9.5 parts of composite admixture; 165-175 parts of water. The conductive enhancer is evenly dispersed in the slurry to form a large conductive network, making the concrete conductive. The conductive enhancer is 10-90nm carbon black powder. Too large a particle size of the carbon black powder may lead to uneven dispersion in the concrete slurry, forming a local area with poor or excessive conductivity, affecting the overall conductive performance, and carbon black is essentially hydrophilic, which means that carbon black will increase the water absorption of concrete and reduce its durability. Summary of the invention
[0005] In order to solve the problem of poor conductivity and hydrophobicity of concrete obtained by admixture additives in the prior art, the present application provides a multifunctional admixture additive based on industrial solid waste and a preparation and use method thereof. Through the carbon nanotube-fly ash composite material and the modification of fly ash, the concrete has good conductivity and good waterproof performance, thereby improving the comprehensive performance of the concrete.
[0006] The present application provides a method for preparing a multifunctional admixture additive based on industrial solid waste, comprising the following steps: S1. Soak fly ash in a nickel nitrate hexahydrate solution with ethanol as the solute for 10-20 minutes, stir the mixture and heat it at a temperature of 50°C-55°C until the alcohol is completely evaporated.
[0007] S2, introducing nitrogen and hydrogen into the reactor at 450°C for 60-80 minutes, then adjusting the temperature to 400-500°C, introducing acetylene, reacting for 45-60 minutes, and then cooling to room temperature under a nitrogen atmosphere to obtain a component A carbon nanotube-fly ash composite material; S3. Take untreated fly ash again, add stearic acid, and dry-ball grind for 8-10 hours to obtain component B hydrophobic fly ash.
[0008] Furthermore, the fly ash includes 50%-70% silicon dioxide, 5%-8% calcium oxide, 20%-40% aluminum oxide, and 3%-7% iron oxide.
[0009] Furthermore, the concentration of the nickel nitrate hexahydrate solution in step S1 is 0.05-0.2 mol / L.
[0010] Furthermore, in step S2, the nitrogen usage is 400-600 mL / min, the hydrogen usage is 200-600 mL / min, and the acetylene usage is 100-400 mL / min.
[0011] Furthermore, the dry ball grinding in step S3 uses an alumina grinding medium with a diameter of 10-19 mm, the ratio of alumina to fly ash is 5-8:1, and the weight ratio of fly ash to stearic acid is 60-80:1.
[0012] According to the above preparation method, a multifunctional admixture additive based on industrial solid waste is obtained, and the ratio of the component A to the component B is 1:1-3.
[0013] The method for using the multifunctional admixture additive based on industrial solid waste comprises: uniformly mixing component B with admixture, cement and aggregate, adding component A after adding water, stirring into slurry, pouring, curing, molding and curing to obtain concrete.
[0014] Furthermore, the addition amount of the A and B components is 3%-8% of the total weight of the concrete.
[0015] The beneficial effects of this application are: 1. The preparation method of the multifunctional admixture additive based on industrial solid waste provided by the present application, through impregnation, the nickel ions are adsorbed on the surface of fly ash, and the necessary catalytic active centers are provided for the subsequent growth of carbon nanotubes, which ensures that the carbon nanotubes can grow uniformly on the surface of fly ash, improves the bonding strength between carbon nanotubes and fly ash, and also improves the activity of the surface of fly ash, providing better conditions for the subsequent growth of carbon nanotubes. Nitrogen and hydrogen are introduced into the reactor under high temperature conditions to provide a reducing atmosphere, and acetylene gas is used to provide a carbon source. Under high temperature and reducing atmosphere, acetylene is decomposed to generate carbon atoms, which are deposited and formed into carbon nanotubes under the catalysis of nickel ions on the surface of fly ash. The generated carbon nanotubes are closely combined with fly ash to form a conductive network, which gives concrete conductivity. Stearic acid is a long-chain fatty acid with lipophilicity, which can chemically adsorb with functional groups such as hydroxyl groups on the surface of fly ash. Stearic acid molecules form a hydrophobic film on the surface of fly ash, which significantly improves the hydrophobicity of fly ash, reduces the adsorption of water, and improves the durability of concrete. Through mechanical grinding, the specific surface area of fly ash is increased and the uniform distribution of stearic acid molecules on the surface of fly ash is promoted. Under the action of mechanical force, stearic acid molecules are more firmly adsorbed on the surface of fly ash to form a stable hydrophobic layer, which makes the concrete conductive and has good waterproof performance, thereby improving the comprehensive performance of concrete.
[0016] 2. After evenly mixing component B with raw materials such as cement and aggregate, add an appropriate amount of water and then add component A. Stir to fully disperse the components to ensure that the carbon nanotube-fly ash composite material is evenly distributed in the concrete to form a conductive network. At the same time, the hydrophobic fly ash is well dispersed in the concrete, providing hydrophobic properties, improving the uniformity and performance consistency of the concrete, and reducing local performance differences. The use of industrial solid waste fly ash as raw material realizes the recycling of resources and reduces environmental pollution. Compared with pure new materials, the use of industrial waste to prepare additives reduces production costs.
[0017] 3. Fly ash, as a porous material, has a large specific surface area and can provide a large number of active sites. When used as a substrate for the growth of carbon nanotubes, fly ash can ensure the uniform distribution of catalyst particles. The silicon dioxide in fly ash has a large specific surface area and can provide more active sites, which is conducive to the growth of carbon nanotubes on its surface. Alumina has a high melting point and chemical stability, which can maintain structural stability at high temperatures, providing a stable support platform for the growth of carbon nanotubes, and also helps to improve the dispersibility of fly ash particles, thereby promoting the uniform growth of carbon nanotubes on the fly ash surface; iron oxide is one of the important catalysts for the growth of carbon nanotubes. By providing iron ions, fly ash can promote the formation of carbon nanotubes, accelerate the growth rate of carbon nanotubes, and help control the diameter and length of carbon nanotubes. Due to the porosity and high specific surface area of fly ash, the carbon nanotubes grown on it can be better attached to the substrate. This enhanced bonding force reduces the contact resistance between carbon nanotubes and helps to form a continuous conductive network, thereby improving the overall conductive performance. The silica and alumina in fly ash can play a certain buffering role, reduce thermal stress at high temperatures, and help reduce defects in the growth process of carbon nanotubes. Fewer defects mean that electrons can move more smoothly inside the carbon nanotubes, thereby improving conductivity. DETAILED DESCRIPTION
[0018] The technical scheme of the present invention and its effects are further described below by specific examples. The following examples are only used to illustrate the content of the present invention and are not used to limit the protection scope of the present invention. Simple changes made to the present invention by applying the concept of the present invention are all within the scope of the protection claimed by the present invention.
[0019] The equipment used in the preparation method of the present invention can be the well-known equipment in the art. The raw materials used in the present invention are commercially available unless otherwise specified.
[0020] Example 1 S1. Soak the fly ash in a 0.1 mol / L nickel nitrate hexahydrate solution with ethanol as the solute for 10 minutes, stir the mixture and heat it at 50°C until the alcohol is completely evaporated.
[0021] S2. At 450°C, nitrogen and hydrogen are introduced into the quartz tube reactor for 60 min, with a nitrogen flow rate of 400 mL / min and a hydrogen flow rate of 400 mL / min. Then the temperature is adjusted to 400°C, acetylene is introduced at a flow rate of 200 mL / min, and the reaction is carried out for 45 minutes. Then the introduction of hydrogen and acetylene is stopped, and the mixture is cooled to room temperature under a nitrogen atmosphere to obtain a component A carbon nanotube-fly ash composite material.
[0022] S3. Take untreated fly ash again, add stearic acid, and dry ball grind for 8 hours. The dry ball grinding uses an alumina grinding medium with a diameter of 15 mm, the weight ratio of alumina to fly ash is 8:1, and the weight ratio of fly ash to stearic acid is 60:1, to obtain component B hydrophobic fly ash.
[0023] S4. Mix component B with admixtures, cement and aggregate evenly, add component A after adding water, stir into slurry, pour, cure, shape and solidify to obtain concrete, the weight ratio of component A to component B is 1:1, and the sum of the weight of component A and component B is 3% of the total weight of the concrete.
[0024] Example 2 S1. Soak the fly ash in a 0.2 mol / L nickel nitrate hexahydrate solution with ethanol as the solute for 20 minutes, stir the mixture and heat it at 55°C until the alcohol is completely evaporated.
[0025] S2. At 450°C, nitrogen and hydrogen are introduced into the quartz tube reactor for 80 min, with a nitrogen flow rate of 500 mL / min and a hydrogen flow rate of 600 mL / min. Then, the temperature is maintained at 450°C, acetylene is introduced at a flow rate of 100 mL / min, and the reaction is carried out for 60 minutes. Then, the introduction of hydrogen and acetylene is stopped, and the mixture is cooled to room temperature under a nitrogen atmosphere to obtain a component A carbon nanotube-fly ash composite material.
[0026] S3. Take untreated fly ash again, add stearic acid, and dry ball grind for 10 hours. The dry ball grinding uses an alumina grinding medium with a diameter of 19 mm, the weight ratio of alumina to fly ash is 5:1, and the weight ratio of fly ash to stearic acid is 70:1, to obtain component B hydrophobic fly ash.
[0027] S4. Mix component B with admixtures, cement and aggregate evenly, add component A after adding water, stir into slurry, pour, cure, shape and solidify to obtain concrete. The weight ratio of component A to component B is 1:2, and the sum of the weights of component A and component B is 8% of the total weight of the concrete.
[0028] Example 3 S1. Soak the fly ash in a 0.05 mol / L nickel nitrate hexahydrate solution with ethanol as the solute for 15 minutes, stir the mixture and heat it at 50°C until the alcohol is completely evaporated.
[0029] S2. At 450°C, nitrogen and hydrogen are introduced into the quartz tube reactor for 70 min, with a nitrogen flow rate of 600 mL / min and a hydrogen flow rate of 200 mL / min. The temperature is then adjusted to 500°C, and acetylene is introduced at a flow rate of 400 mL / min. The reaction is carried out for 55 minutes, and then the introduction of hydrogen and acetylene is stopped. The mixture is cooled to room temperature under a nitrogen atmosphere to obtain a component A carbon nanotube-fly ash composite material.
[0030] S3. Take untreated fly ash again, add stearic acid, and dry ball grind for 9 hours. The dry ball grinding uses an alumina grinding medium with a diameter of 10 mm, the weight ratio of alumina to fly ash is 7:1, and the weight ratio of fly ash to stearic acid is 80:1, to obtain component B hydrophobic fly ash.
[0031] S4. Mix component B with admixtures, cement and aggregate evenly, add component A after adding water, stir into slurry, pour, cure, shape and solidify to obtain concrete, the weight ratio of component A to component B is 1:3, and the sum of the weight of component A and component B is 5% of the total weight of the concrete.
[0032] Comparative Example 1 S1. Take untreated fly ash, add stearic acid, and dry ball grind for 9 hours. The dry ball grinding uses an alumina grinding medium with a diameter of 10 mm, the weight ratio of alumina to fly ash is 7:1, and the weight ratio of fly ash to stearic acid is 80:1 to obtain component B hydrophobic fly ash.
[0033] S2. Mix component B with admixtures, cement and aggregate evenly, add water and then add component A, where component A is carbon nanotubes sold by Guangzhou Jiushun New Materials Co., Ltd., stir into slurry, pour, cure, shape and solidify to obtain concrete, the weight ratio of component A to component B is 1:3, and the sum of the weights of component A and component B is 5% of the total weight of the concrete.
[0034] Comparative Example 2 S1. Soak the fly ash in a 0.2 mol / L nickel nitrate hexahydrate solution with ethanol as the solute for 20 minutes, stir the mixture and heat it at 55°C until the alcohol is completely evaporated.
[0035] S2. At 450°C, nitrogen and hydrogen are introduced into the quartz tube reactor for 80 min, with a nitrogen flow rate of 500 mL / min and a hydrogen flow rate of 600 mL / min. The temperature is then raised to 600°C, and acetylene is introduced at a flow rate of 100 mL / min. The reaction is carried out for 60 minutes, and then the introduction of hydrogen and acetylene is stopped. The mixture is cooled to room temperature under a nitrogen atmosphere to obtain a component A carbon nanotube-fly ash composite material.
[0036] S3. Take untreated fly ash again, add stearic acid, and dry ball grind for 10 hours. The dry ball grinding uses an alumina grinding medium with a diameter of 19 mm, the weight ratio of alumina to fly ash is 5:1, and the weight ratio of fly ash to stearic acid is 70:1, to obtain component B hydrophobic fly ash.
[0037] S4. Mix component B with admixtures, cement and aggregate evenly, add component A after adding water, stir into slurry, pour, cure, shape and solidify to obtain concrete. The weight ratio of component A to component B is 1:2, and the sum of the weights of component A and component B is 8% of the total weight of the concrete.
[0038] Comparative Example 3 S1. Soak the fly ash in a 0.1 mol / L nickel nitrate hexahydrate solution with ethanol as the solute for 10 minutes, stir the mixture and heat it at 50°C until the alcohol is completely evaporated.
[0039] S2. At 450°C, nitrogen and hydrogen are introduced into the quartz tube reactor for 60 min, with a nitrogen flow rate of 400 mL / min and a hydrogen flow rate of 400 mL / min. Then the temperature is adjusted to 400°C, acetylene is introduced at a flow rate of 200 mL / min, and the reaction is carried out for 45 minutes. Then the introduction of hydrogen and acetylene is stopped, and the mixture is cooled to room temperature under a nitrogen atmosphere to obtain a component A carbon nanotube-fly ash composite material.
[0040] S3. Take untreated fly ash again, add stearic acid, and dry ball grind for 8 hours. The dry ball grinding uses an alumina grinding medium with a diameter of 15 mm, the weight ratio of alumina to fly ash is 8:1, and the weight ratio of fly ash to stearic acid is 60:1, to obtain component B hydrophobic fly ash.
[0041] S4. Mix component B with admixtures, cement and aggregate evenly, add component A after adding water, stir into slurry, pour, cure, shape and solidify to obtain concrete, the weight ratio of component A to component B is 1:1, and the sum of the weights of component A and component B is 10% of the total weight of the concrete.
[0042] Comparative Example 4 S1. Soak the fly ash in a 0.2 mol / L nickel nitrate hexahydrate solution with ethanol as the solute for 20 minutes, stir the mixture and heat it at 55°C until the alcohol is completely evaporated.
[0043] S2. At 450°C, nitrogen and hydrogen are introduced into the quartz tube reactor for 80 min, with a nitrogen flow rate of 500 mL / min and a hydrogen flow rate of 600 mL / min. Then, the temperature is maintained at 450°C, acetylene is introduced at a flow rate of 100 mL / min, and the reaction is carried out for 60 minutes. Then, the introduction of hydrogen and acetylene is stopped, and the mixture is cooled to room temperature under a nitrogen atmosphere to obtain a component A carbon nanotube-fly ash composite material.
[0044] S3. Take untreated fly ash again, add stearic acid, and dry ball grind for 10 hours. The dry ball grinding uses an alumina grinding medium with a diameter of 19 mm, the weight ratio of alumina to fly ash is 5:1, and the weight ratio of fly ash to stearic acid is 70:1, to obtain component B hydrophobic fly ash.
[0045] S4. Mix component B with admixtures, cement and aggregate evenly, add component A after adding water, stir into slurry, pour, cure, shape and solidify to obtain concrete, the weight ratio of component A to component B is 1:5, and the sum of the weight of component A and component B is 8% of the total weight of the concrete.
[0046] The concrete obtained in the embodiment and the comparative example was poured into a mold with a size of 100 mm × 100 mm × 100 mm. One part of the samples was used for resistivity and water contact angle tests, and the other part of the samples was used for compressive strength tests. The test results are shown in the following table.
[0047] Table 1: Performance test table of samples obtained in specific implementation methods From the data in the above table, it can be seen that the conductivity of Examples 1-3 is better than that of Comparative Examples 1-3. The difference between Comparative Example 1 and Example 3 is that the carbon nanotubes use commercial products, and it can be seen that their resistivity is much higher than that of the carbon nanotubes deposited using fly ash as the base. Compared with Example 2, the reaction temperature of Comparative Example 2 is 600°C, and its resistivity and hydrophobicity are worse than those of Example 2. Compared with Example 1, the weight of additives A and B components in Comparative Example 3 accounts for 10% of the total weight of concrete, and its resistivity is worse than that of Example 1, and its hydrophobicity is basically the same as that of Example 1. Compared with Example 2, the weight ratio of component A to component B in Comparative Example 4 is 1:5, and the resistivity of Comparative Example 4 is worse than that of Example 2, but its hydrophobicity is better than that of Example 2, because the specific gravity of hydrophobic fly ash increases. In terms of compressive strength, there is little difference in the performance between Examples 1-3 and Comparative Examples 1, 2, and 4, but the compressive strength of Comparative Example 3 is significantly lower than that of other specific embodiments, because the proportion of additives in the total weight of concrete is too large.
Claims
1. A method for preparing a multifunctional admixture additive based on industrial solid waste, characterized in that: The following steps are involved: S1. Soak fly ash in a nickel nitrate hexahydrate solution with ethanol as the solute for 10-20 minutes, stir the mixture and heat it at a temperature of 50°C-55°C until the alcohol is completely evaporated; S2, introducing nitrogen and hydrogen into the reactor at 450°C for 60-80 minutes, then adjusting the temperature to 400-500°C, introducing acetylene, reacting for 45-60 minutes, and then cooling to room temperature under a nitrogen atmosphere to obtain a component A carbon nanotube-fly ash composite material; S3. Take untreated fly ash again, add stearic acid, and dry-ball grind for 8-10 hours to obtain component B hydrophobic fly ash.
2. The method for preparing the multifunctional admixture additive based on industrial solid waste according to claim 1, characterized in that: The fly ash comprises 50%-70% silicon dioxide, 5%-8% calcium oxide, 20%-40% aluminum oxide and 3%-7% iron oxide.
3. The method for preparing the multifunctional admixture additive based on industrial solid waste according to claim 1, characterized in that: The concentration of the nickel nitrate hexahydrate solution in step S1 is 0.05-0.2 mol / L.
4. The method for preparing the multifunctional admixture additive based on industrial solid waste according to claim 1, characterized in that: In step S2, the nitrogen dosage is 400-600 mL / min, the hydrogen dosage is 200-600 mL / min, and the acetylene dosage is 100-400 mL / min.
5. The method for preparing a multifunctional admixture additive based on industrial solid waste according to claim 1, characterized in that: The dry ball grinding in step S3 uses an alumina grinding medium with a diameter of 10-19 mm, the ratio of alumina to fly ash is 5-8:1, and the mass ratio of fly ash to stearic acid is 60-80:
1.
6. A multifunctional admixture additive based on industrial solid waste is obtained according to the preparation method of the multifunctional admixture additive based on industrial solid waste according to any one of claims 1 to 5.
7. The multifunctional admixture additive based on industrial solid waste according to claim 6, characterized in that: The ratio of component A to component B is 1:1-3.
8. The multifunctional admixture additive based on industrial solid waste according to claim 6, characterized in that: The addition amount of the A and B components is 3%-8% of the total weight of the concrete.
9. The method for using the multifunctional admixture additive based on industrial solid waste according to claim 6, characterized in that: Mix component B with admixtures, cement and aggregates evenly, add component A after adding water, stir into slurry, pour, cure, shape and solidify to obtain concrete.
Citation Information
Patent Citations
Fly ash surface modification method and application in water-proof mortar
CN101386485A
Mineral admixture for concrete and preparation method thereof
CN113173723A
Method for synchronously improving mechanical property and moisture transmission property of large-volume fly ash mortar by using chemical admixture
CN116986871A
All-solid-waste zero-carbon concrete and preparation method thereof
CN117602878A
Method for preparing single-walled carbon nanotube based on fly ash
CN117682508A
